Rancang Bangun Mesin Stapler Siku Kayu Fleksibel Dua Sisi dengan Sistem Elektropneumatik pada Perusahaan Manufaktur Mebel - Kholiqul Misbah; Heroe Poernomo; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
PT. Marufuji Kenzai Indonesia one of furniture manufacture company in east java which use elbow stapler machine to assist production process. This elbow stapler machine is used to unite the elbow portion of the fiberboard (hardboard) material. However, the elbow stapler machine used is only able to be used to unite one side only. This of course inhibits the production process considering the number of stapler engines is not proportional to the number of fiber board material (hardboard) that is done. The method used to overcome the problem of delay in the work of fiberboard material (hardboard) is to make a two-sided flexible wooden elbow stapler machine using electropneumatic system. The working system of this machine will use three pneumatic cylinders where two cylinders are used for the stapler and one large cylinder is used to push the stapled material. Making this machine will be through several stages such as design, detail drawing, framework analysis, simulation, electropneumatic system design, to the assembly stage (assembly). Making the flexible wooden elbow stapler machine is expected to be able to overcome the problems that often occur in the process stapler material that has been produced. So that the work is usually done by one operator can be helped by the performance of this flexible wooden elbow stapler machine. So no more stacking of material in the stapler that resulted in disruption of some further process.